Hydrogenation of Quinolines Using a Recyclable Phosphine-Free Chiral Cationic Ruthenium Catalyst: Enhancement of Catalyst Stability and Selectivity in an Ionic Liquid - Zhou, Haifeng; Li, Zhiwei; Wang, Zhijian; Wang, Tianli; Xu, Lijin; He, Yanmei; Fan, Qing-Hua; Pan, Jie; Gu, Lianquan; Chan, Albert S.C (Angewandte Chemie (International ed.), 2008)
Liquid assets: The catalyst (S,S)‐1 exhibits an unprecedented reactivity and excellent enantioselectivity for the title reaction when it is carried out in neat ionic liquid (see scheme; BMIM=1‐n‐butyl‐3‐methylimidazolium, Tf=trifluoromethanesulfonyl, Ts=4‐toluenesulfonyl). The ionic liquid facilitates the catalyst recycling and enhances its stability and selectivity.